Association of low blood pressure with anxiety and depression: the Nord‐Trøndelag Health Study - Hildrum, Bjørn (BMJ Group, 2007)
BACKGROUND: Low blood pressure has mainly been regarded as ideal, but recent studies have indicated an association with depression in elderly people. OBJECTIVE: To investigate whether low blood pressure is associated with anxiety and depression in the general population. DESIGN: Cross‐sectional study. SETTING: Participants in the population‐based Nord‐Trøndelag Health Study (HUNT‐2, 1995–7), Norway. PARTICIPANTS: 60 799 men and women aged 20–89 years filled in the Hospital Anxiety and Depression Scale as part of a general health study. Systolic and diastolic blood pressure was classified in age‐stratified and sex‐stratified centile groups. MAIN RESULTS: Compared with participants with systolic blood pressure within the 41–60 centile (reference) group, the odds ratio for anxiety was 1.31 (95% confidence intervals (CI) 1.16 to 1.49), for depression 1.22 (95% CI 1.03 to 1.46), and for comorbid anxiety and depression 1.44 (95% CI 1.24 to 1.68) in the group with ⩽5 centile systolic blood pressure. Slightly weaker associations were found of low diastolic blood pressure with anxiety and depression. These associations were similar across sex and age groups. Physical impairment, smoking and angina pectoris influenced the associations only marginally, whereas stroke, myocardial infarction, use of drugs for hypertension, body mass index and several other covariates had no influence. CONCLUSIONS: This study represents epidemiological evidence for an association of low blood pressure with anxiety and depression, which is not caused by cardiovascular disease.